Community Empowerment In Developing Tourist Village in Kenderan Village, Tegallalang Sub-disctrict, Gianyar Regency - Shella Natasya Sri Mutiara Baringbing; I Ketut Winaya; Komang Adi Sastra Wijaya (CV. Lenggogeni Data Publishing, 2023)
The tourism potential in Kenderan Village must be empowered and managed well in order to have a real impact on the community. Efforts that can be made to empower this potential are by empowering the community in developing tourist villages. This is a real form of Indonesian economic development through tourismbased villages. To create good community empowerment, empowerment groups need to be formed. The aim of this research is to find out how community empowerment is in developing tourist villages in Kenderan Village. This research uses qualitative research with a descriptive approach. The data collection uses observation, interviews and documentation methods. The data sources used are primary data and secondary data. The technique for determining informants in this research used purposive sampling. By using Community Empowerment Theory according to Mardi Yatmo Hutomo (2000: 7-10) with five types of community empowerment, namely, 1). Capital Assistance, which explains that there is financial assistance from the APBDes for community empowerment and development of tourist villages. 2). Infrastructure Assistance, explained that assistance had been implemented in the form of marketing platforms for empowerment groups and development of tourism supporting infrastructure. 3). Mentoring Assistance, explaining that there is training and assistance for business groups and tourism actors. 4). Institutional strengthening, with the formation of the Pokdarwis institution. 5). Strengthening Partnerships, collaboration from third parties. The results of this research explain that all indicators have worked but not optimally. So for sustainability it is necessary to strengthen these five indicators.